Actitudes del docente ante la inclusión de un estudiante con necesidades educativas especiales - Cerna Vinueza, Natalia Viviana (2019)
This investigation presents the case of a 17-year-old patient with male epilepsy with difficulties in some basic subjects. A theoretical review was made about inclusive education as a process in which all the members of the community for each of them participate in their contribution to a better confrontation of the educational process. The teacher's attitude was highlighted as a relevant factor regarding the inclusion of students with special educational needs. Collection techniques were used such as the clinical interview, test application, among others, with which the patient's symptoms were analyzed, and the possible diagnosis was determined: Learning Disorders F81. (CIE-10). Psychoeducation was applied to the patient, with social skills training techniques, in addition to performing restorative circles, which contributed to the student's academic condition.